2022
DOI: 10.1155/2022/1429932
|View full text |Cite
|
Sign up to set email alerts
|

Cause-Effect Relationships between Painful TMD and Postural and Functional Changes in the Musculoskeletal System: A Preliminary Report

Abstract: Introduction. Temporomandibular disease (TMD) is a general term including a group of conditions that cause pain and dysfunction in the masticatory muscles, the temporomandibular joint (TMJ), and their related structures. The painful forms of these dysfunctions have become an increasing phenomenon among dental patients. A number of scientific publications indicated the relationship between the presence of postural dysfunctions and functional disorders of the masticatory system in humans. Nevertheless, dental pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Almoznino et al ( 53 ) investigated the long-term adherence of patients to occlusal splints and reported that those with mild to major pain reduction had higher adherence rates compared with those with no or complete pain relief. Moreover, Garstka et al ( 54 ) demonstrated that physical manifestations of TMDs are on the rise amongst individuals and posture disturbances and associated functional disorders are associated. Consequently, the diagnosis and medical therapy of patients with TMD ought to be comprehensive.…”
Section: Discussionmentioning
confidence: 99%
“…Almoznino et al ( 53 ) investigated the long-term adherence of patients to occlusal splints and reported that those with mild to major pain reduction had higher adherence rates compared with those with no or complete pain relief. Moreover, Garstka et al ( 54 ) demonstrated that physical manifestations of TMDs are on the rise amongst individuals and posture disturbances and associated functional disorders are associated. Consequently, the diagnosis and medical therapy of patients with TMD ought to be comprehensive.…”
Section: Discussionmentioning
confidence: 99%
“…At the Department of Propaedeutics, Physical diagnostics, and Dental Physiotherapy, the treatment team consists of an orthodontist, a physician dealing with dental prosthetics and restorative dentistry, a physiotherapist, and a dentist who coordinates the work of the whole team [ 114 ]. One of the most common signs of a disease process within the TMJ are sounds emitted by the articular structures, such as popping, clicking, humming, grinding, or crunching [ 114 ].…”
Section: The Essence Of the Mattermentioning
confidence: 99%
“…Temporomandibular disorders (TMDs), with a reporting prevalence between 28% and 88%, are common in young people aged 20 to 40 years and in female [ 1 ]. TMD is a comprehensive disease involving joints, muscles, and nerves, which is mainly characterized by the restriction, deviation, and deflection of mandibular movement, clicking sound of temporomandibular joint (TMJ), and pain in masticatory muscles, anterior ear, and the TMJ region [ 2 – 4 ].…”
Section: Introductionmentioning
confidence: 99%